Endometriosis Is Undervalued: A Call to Action - Ellis, Katherine; Munro, Deborah; Clarke, Jennifer (Frontiers in Global Women's Health, 2022)
Endometriosis is an inflammatory chronic pain condition caused by uterine tissue growing outside of the uterus that afflicts at least 11% of women (and people assigned female at birth) worldwide. This condition results in a substantial burden to these women, and society at large. Although endometriosis was first identified over 160 years ago, substantial knowledge gaps remain, including confirmation of the disease's etiology. Research funding for endometriosis is limited, with funding from bodies like the National Institutes of Health (NIH) constituting only 0.038% of the 2022 health budget—for a condition that affects 6.5 million women in the US alone and over 190 million worldwide. A major issue is that diagnosis of endometriosis is frequently delayed because surgery is required to histologically confirm the diagnosis. This delay increases symptom intensity, the risk of central and peripheral sensitization and the costs of the disease for the patient and their nation. Current conservative treatments of presumed endometriosis are pain management and birth control. Both of these methods are flawed and can be entirely ineffective for the reduction of patient suffering or improving ability to work, and neither addresses the severe infertility issues or higher risk of certain cancers. Endometriosis research deserves the funding and attention that befits a disease with its substantial prevalence, effects, and economic costs. This funding could improve patient outcomes by introducing less invasive and more timely methods for diagnosis and treatment, including options such as novel biomarkers, nanomedicine, and microbiome alterations.